Effect of positive thinking intervention based on multimedia program on psychological security and life expectancy in patients with COVID-19 - Shahla Teymoori Korrani; Shahram Etemadifar; Shahnaz Nemati; Hadi Raeisi; Bita Sadeghi (Journal of Education and Health Promotion)
BACKGROUND: The coronavirus disease 2019 (COVID-19), both novel and highly contagious, originated in Wuhan, China. It can cause psychological distress, leading to feelings of insecurity and hopelessness. Thus, this study aims to explore how a multimedia-based positive thinking program can impact the psychological security and life expectancy of COVID-19 patients. MATERIALS AND METHODS: This study employed a semi-experimental, two-group pretest-posttest design. Participants were chosen through convenience sampling from Hajar and Seyed Al-Shohada’ Farsan hospitals affiliated with Shahrekord University of Medical Sciences from 2022 to 2023. A total of 70 patients were assigned randomly to two groups of 35 each, intervention and control. Data collection tools included a demographic information questionnaire, Maslow’s Psychological Security Questionnaire, and Schneider’s Life Expectancy Questionnaire. Data analysis was performed using the Statistical Package for the Social Science (SPSS) version 23, utilizing the paired t-test, independent t-test, and repeated-measures analysis of variance (ANOVA). RESULTS: Before the interventions, the mean scores of psychological security and life expectancy, respectively, in the control group were 45.7 ± 7.2 and 44.7 ± 7.8 and in the intervention group were 44 ± 1.39 and 39.0 ± 11.0. These two groups had no significant difference in these regards. Immediately after the interventions, the mean scores of psychological security and life expectancy, respectively, in the control group were 45.8 ± 6.9 and 44.8 ± 3.8 and in the intervention group were 49.2 ± 1.9 and 45.2 ± 10.9, and 1 month after the intervention, the mean scores of psychological security and life expectancy, respectively, in the control group were 47 ± 0.47 and 47.0 ± 8.4 and in the intervention group were 57 ± 0.51 and 54.5 ± 6.4. The two study groups had significant difference regarding the mean scores of psychological security and life expectancy immediately and 1 month after interventions (P < 0.001). Generally, after the positive thinking intervention, the mean scores of dependent variables increased in both groups, with greater changes observed in the intervention group. CONCLUSION: The results of this study showed that an intervention program based on positive thinking could improve the level of life expectancy and mental security of patients with COVID-19. Therefore, to enhance the mental security and life expectancy of these patients, it is suggested that institutions, such as the Ministry of Health, and healthcare providers, such as nurses, pay attention to the effect of emerging supportive treatments and teaching these programs to patients, such as treatment based on positive psychology. This will enable people to deal with difficult situations by improving their psychological structures and promoting higher levels of well-being and mental health for patients by health policymakers.